Innovative Utilization Possibilities of Industrial Wastes from Hungary as Construction Industrial Material - Mucsi, Gábor; Szabó, Roland; Rácz, Ádám; Papné Halyag, Nóra; Nagy Gáborné Ambrus, Mária; Debreczeni, Ákos; Móricz, Ferenc; Kristály, Ferenc (International Journal of Engineering and Management Sciences, 2019)
The research results carried out at the University of Miskolc Faculty of Earth Science and Engineering in the Center of Excellence of Sustainable Natural Resource Management show that the physical and mechanical properties of the construction industrial products (strength, compactness) made of waste sources can be controlled reasonably by the appropriate processing technologies and under optimized circumstances and characteristics (particle size distribution, specific surface area). It was established that beside the chemical activation, the mechanical activation of solids is an effective tool for improving the product characteristics. However, this modifies the physical as well as structural, mineralogical properties of the raw materials, therefore its determination is of great importance.